2022
DOI: 10.3390/jpm12101697
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Carotid Artery Stenosis and Atherosclerotic Cardiovascular Disease in Patients with Calcium Kidney Stone: Assessment of Systemic Inflammatory Biomarkers

Abstract: (1) Background: To assess the clinical significance of preoperative inflammatory biomarkers combined with atherosclerotic cardiovascular disease (ASCVD) risk score to evaluate carotid artery stenosis in patients with calcium kidney stones; (2) Methods: We conducted a prospective observational case-control study, enrolling 74 patients with calcium kidney stones and 66 age- and sex-matched healthy controls. We calculated the inflammatory biomarkers including the neutrophil-lymphocyte ratio (NLR), monocyte-lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The authors concluded that red blood cell distribution width and NLR could serve as predictors of traditional and novel markers of vascular calcification and CV disease [20]. Similarly, in a study that enrolled 74 patients, calcium kidney stones were associated with higher levels of inflammatory biomarkers, including NLR, MLR, and SIRI, compared with ageand sex-matched non-stone formers [21]. Also, in this report, after stratification by CV risk category, all inflammatory biomarkers and the severity of carotid artery stenosis were still significantly higher in calcium stone formers.…”
Section: Discussionmentioning
confidence: 97%
“…The authors concluded that red blood cell distribution width and NLR could serve as predictors of traditional and novel markers of vascular calcification and CV disease [20]. Similarly, in a study that enrolled 74 patients, calcium kidney stones were associated with higher levels of inflammatory biomarkers, including NLR, MLR, and SIRI, compared with ageand sex-matched non-stone formers [21]. Also, in this report, after stratification by CV risk category, all inflammatory biomarkers and the severity of carotid artery stenosis were still significantly higher in calcium stone formers.…”
Section: Discussionmentioning
confidence: 97%